SISTEM PENDUKUNG KEPUTUSAN REKOMENDASI PEMILIHAN STUDIO MUSIK - Dimas Nando Putro Widodo; Indah Puji Astuti; Ghulam Asrofi Buntoro (JuSiTik : Jurnal Sistem dan Teknologi Informasi Komunikasi, 2022)
Determining where to practice music (music studio) according to the wishes of each person is not easy. Before deciding which studio to rent, first look for information about music studio rental locations, then compare and select the studio according to the criteria. From this, a decision support system can be developed to determine the right place to rent a music studio using the SAW (Simple Additive Weighting) method. This study uses the SAW method, because the method is faster to use, simple and specific, and the weighting is directly focused on the weight value and ranking is carried out. The criteria needed for decision making are price, studio location, number of studios, completeness of equipment, studio area, and facilities. The results of this study produce recommendations for the best alternative for the selection of a music studio in Ponorogo.